2018
DOI: 10.1364/ome.8.001902
|View full text |Cite
|
Sign up to set email alerts
|

Processing and fabrication of micro-structures by multiphoton lithography in germanium-doped arsenic selenide

Abstract: This work reports the processing and properties of a new chalcogenide glass film that can be photo-patterned by multiphoton lithography (MPL) with enhanced post-fabrication stability. Thermally evaporated germanium-doped arsenic selenide [Ge 5 (As 2 Se 3) 95 ] thin films were photo-patterned using the output of a mode-locked titanium:sapphire laser. The morphology, chemical structure, and optical properties of the material were studied before and after photo-patterning and compared for their long-term aging be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Laser‐processed chalcogenide glasses (ChGs) have been investigated as a means for creating infrared (IR) functional devices . ChGs are materials that are mostly made of one or more of the following chalcogen elements: sulfur (S), selenium (Se), and tellurium (Te), but excluding oxygen (O).…”
Section: Femtosecond Direct Laser Writing and Chemical Etching In Optmentioning
confidence: 99%
See 4 more Smart Citations
“…Laser‐processed chalcogenide glasses (ChGs) have been investigated as a means for creating infrared (IR) functional devices . ChGs are materials that are mostly made of one or more of the following chalcogen elements: sulfur (S), selenium (Se), and tellurium (Te), but excluding oxygen (O).…”
Section: Femtosecond Direct Laser Writing and Chemical Etching In Optmentioning
confidence: 99%
“…As 2 S 3 has high transparency in the IR (620 nm to 11 μm), an optical bandgap of E g = 2.35 eV ( λ = 517 nm), high refractive index ( n ∼ 2.45‐2.53), and potential for optical applications . Raman spectroscopy has shown that thermal deposition of As 2 S 3 breaks the bulk network solid into As 4 S 4 , As 4 S 6 , and S 8 molecular clusters . The As 2 S 3 films are most photosensitive if they contain a high fraction of these molecular clusters with homopolar bonds .…”
Section: Femtosecond Direct Laser Writing and Chemical Etching In Optmentioning
confidence: 99%
See 3 more Smart Citations